Survival of Patients With Short‐Bowel Syndrome on Home Parenteral Nutrition: A Prospective Cohort Study. Issue 5 (3rd September 2020) - Noelting, Jessica; Gramlich, Leah; Whittaker, Scott; Armstrong, David; Marliss, Errol; Jurewitsch, Brian; Raman, Matreyi; Duerksen, Donald R.; Stevenson, Danielle; Lou, Wendy; Saha, Sudipta; Allard, Johane P.
Abstract: Background: Survival of patients with short‐bowel syndrome (SBS) receiving home parenteral nutrition (HPN) and associated factors have not been reported recently in North America. The objective of this study was to determine the long‐term survival of adult patients with SBS as the primary indication for HPN and assess factors that may affect survival by using the Canadian HPN Registry. Methods: This is a retrospective analysis of prospectively collected data extracted from the HPN registry, prior to approval of teduglutide in Canada. Using only incident cases, survival probabilities were estimated by using the Kaplan‐Meier method for both full‐cohort and nonmalignant SBS. Log‐rank test was also used to test the differences in survival distributions between subgroups in the univariate analysis. To identify potential variables that are affecting survival distribution of patients for the multivariable analysis, Least Absolute Shrinkage and Selection Operator and stepwise selection procedure were used. Results: There were 321 patients with a known duration receiving HPN (total, 2287 years), of whom 218 were entered into the registry within 1 year of initiation of HPN. Of 218 incident cases, 22 had active malignancy, along with SBS, and their survival time was significantly lower than those with nonmalignant SBS ( P ‐value < .0001). The 5‐year survival of nonmalignant‐SBS patients was 81.9%. In this subgroup, there was no significant association between patients' survival and known intestinal anatomy, age, or sex. Conclusion: Patients with nonmalignant SBS who receive HPN have a 5‐year survival of >80%. Known intestinal anatomical factors did not affect survival.